(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The topics of adolescent delinquency and access to legal aid take centre stage in this piece. TheAct makes it mandatory for individuals of any age to have legal representation. In 1973, the government ofIndia appointed Krishna Iyer to head a committee that would investigate the possibility of the statesdeveloping and implementing their own individual legal aid systems. The Committee recommended thatthe principle of providing citizens with access to legal aid be included into the constitution. As a directconsequence of this, Article 31-A was inserted into the Principles of State Policy Directives. TheCommittee for the Implementation of Legal Aid Services (CILAS) was established by the CentralGovernment in 1980, and it is still in operation to the present day.